The equation of the parabola in the vertex form is y = (x - 3
- 5 with ( 3, -5) is the vertex of the parabola and 1 is the multiplier
In the above question, A parabolic equation is given as follows:
Y = x^2 - 6x + 4
The equation of the parabola in the vertex form is :
y = a (x - h
+ k
Where a is a multiplier in the equation and (h,k) are the coordinates of the vertex
So, in order to obtain this form, we will use the method of completing square :
Y = x^2 - 6x + 4
y =
- 6x + (9 -9) + 4
y = (x - 3
+ ( -9 + 4)
y = (x - 3
- 5
where, ( 3, -5) is the vertex of the parabola and 1 is the multiplier
Hence, The equation of the parabola in the vertex form is y = (x - 3
- 5 with ( 3, -5) is the vertex of the parabola and 1 is the multiplier
To learn more about, parabola, here
brainly.com/question/21685473
#SPJ1
Answer: m∠ M′N′O′ = 90 degrees
Step-by-step explanation: Hope that helps ! I am not sure if I am right but I think I am !
X=-1 is the answer. Hope that helps!
Answer:
The equation that represents the new path is y=(1/2)x-2
Step-by-step explanation:
step 1
Find the slope of the give line
we have
y=-2x-7
so
the slope m is equal to
m=-2
step 2
Find the slope of the perpendicular line to the given line
Remember that
If two lines are perpendicular, then their slopes are opposite reciprocal of each other
so
we have
m=-2 -----> slope of the given line
therefore
The slope of the perpendicular line is equal to
m=1/2
step 3
With m=1/2 and the point (-2,-3) find the equation of the line
y-y1=m(x-x1)
substitute
y+3=(1/2)(x+2)
y=(1/2)x+1-3
y=(1/2)x-2 -----> equation that represent the new path
Answer:
the answer is 44cm3
Step-by-step explanation:
you're welcome